Silence in Hanover Close - Perry, Anne (Perry, Anne. Charlotte and Thomas Pitt novel., 2011)
When Inspector Thomas Pitt is asked to reopen a three-year-old murder case that had taken place in London<U+2019>s luxurious Hanover Close, he is all too aware that his superiors want him to simply smooth things over. But penetrating the reserve of high society households will take more finesse than Pitt can muster. Enter Charlotte Pitt, his wellborn wife, and her sister, Emily. As the social equals of the inhabitants of the Close, the women are privy to conversations that would never reach the ears of a mere policeman. What they find is a secret so shocking it will lead to more deaths<U+2014>including, quite possibly, Pitt<U+2019>s own.